Milk, Honey, Pollen. Time and Sensorial Experiences in the Work of Wolfgang Laib: la chambre des certitudes - Jiménez-Donaire Martínez, Salvador (Espacio Tiempo y Forma. Serie VII, Historia del Arte, 2021)
Wolfgang Laib’s oeuvre spans through more than three decades and the artist has become one of the most respected figures in the contemporary scene. Profoundly spiritual and imbued with a sense of rituality, his practice includes elements of performance, sculpture and minimal and conceptual art, in addition to references to Jainism, Christianism and Hinduism. Employing mainly natural materials such as milk, pollen, rice and honeybee, his body of work is both sensual and fragile. This text analyses Laib’s art proposals not as objects but as a sensorial, physical experience, focusing on their fragrant, haptic and highly aesthetic qualities. In order to do so, one of Laib’s lesser known projects are examined here: a beeswax chamber in the French Pyrenees. Ultimately, this text argues that by virtue of patience, perseverance and continuity, Laib’s art process offers a prolonged, transformative temporal conception through contemplation, immersion and sensoriality.